Patient’s Perspective on Doctor’s Outfit: A Descriptive Study in a Tertiary Hospital of Nepal - Timilsina, Sangita; Pokharel, Bibesh; KC, Rajan; Gajurel, Sharad Hari (Annapurna Journal of Health Sciences, 2026)
Background: Physician attire significantly influences patient perceptions and attitudes. In the absence of standardized dress codes, understanding patient preferences can help improve doctor-patient relationships and healthcare delivery. Methods:A descriptive observational study was conducted from July 1 to August 15, 2023, at a tertiary hospital in Nepal. Patients and their relatives attending the outpatient clinic completed a questionnaire after taking proper consent. Participants assessed six sets of physician attire based on trustworthiness, approachability, comfort, and perceived knowledgeability. Results: The majority preferred physicians wearing scrubs with a white coat, name-tag, and stethoscope, associating this with professionalism (79.1%) and responsibility (74.8%). Additionally, 53.2% believed attire reflected physician competence. The white coat was favored by 94.3% of participants for professionalism (34.8%) and identification (33.7%), though 83.3% opposed its use outside healthcare settings due to cleanliness concerns. Scrubs with a white coat and stethoscope were linked to trustworthiness, safety, and knowledgeability across both genders. Conclusion: Physician attire plays a crucial role in shaping patient perceptions, with a strong preference for scrubs and a white coat. Implementing attire guidelines based on patient preferences could enhance healthcare interactions.